2007
DOI: 10.3892/or.17.6.1279
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic DNA-methylation regulation of genes coding for lipid raft-associated components: A role for raft proteins in cell transformation and cancer progression (Review)

Abstract: Abstract. Metastatic progression is the cause of most cancer deaths. Host tumour cell separation (fission) is accompanied by simultaneous acquisition of migrating capability of cancer cells, remodeling of cellular architecture and effective 'homing' in body host environment. Cell remodeling involves cytoskeletal protein-protein and lipid-protein interaction together with altered signaling. Alteration of signaling in tumour cells may affect expression of many genes also by DNAmethylation/demethylation. This wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 94 publications
(257 reference statements)
2
57
0
Order By: Relevance
“…The expression of uPAR is cancer stage specific [46]. uPAR is an adhesion receptor for vitronectin and also interacts with integrin b-chains.…”
Section: Cd44mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of uPAR is cancer stage specific [46]. uPAR is an adhesion receptor for vitronectin and also interacts with integrin b-chains.…”
Section: Cd44mentioning
confidence: 99%
“…Proteolysis of extracellular matrix proteins modifies integrin-mediated anchorage, focal adhesion and cytoskeletal archi tecture, thereby triggering signaling molecules such as FAK [47] and motility factors such as autocrine motility factor/phosphohexose isomerase PHI [48]. It has been shown that matrix metalloproteinase and uPAR expression is controlled at the transcription level by DNA methylation and demethylation [46].…”
Section: Cd44mentioning
confidence: 99%
“…These membranes are involved in receptor-independent endocytosis. Caveolae are microdomains of lipid rafts, which are rich in sphingolipids and cholesterol and play an essential role in the degradation of cholesterol (14). However, they also participate in transmembrane signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Many proteins, such as H-Ras, caveolin-1, CD44, Fas, Fas-associated death domain protein, uPAR, epidermal growth factor receptor (EGFR), integrins, and catenins, conduct their function in lipid rafts (3,4). Although being important structural components for delivering lipids and proteins, lipid rafts have also been reported by numerous studies to be involved in the development and progression of cancer (5,6). For instance, the cholesterol-enriched lipid raft, containing proteins such as caveolins, CD44, and members of the receptor tyrosine kinase family, induces cell transformation, tumor progression, angiogenesis, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the cholesterol-enriched lipid raft, containing proteins such as caveolins, CD44, and members of the receptor tyrosine kinase family, induces cell transformation, tumor progression, angiogenesis, and metastasis. The sphingolipidenriched lipid raft, containing FAS, FASL, and death-inducing signaling complex proteins prevent cells from apoptosis (5,6). Therefore, lipid rafts have been recently suggested to be new therapeutic targets and intervention strategies against cancer (7,8).…”
Section: Introductionmentioning
confidence: 99%